Pendidikan Karakter Perspektif Al-Qur’an - Sulaiman, Sulaiman (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2019)
Character education has become the focus of attention lately because of a setback that has resulted in moral decline. In the Qur'an, characters use the term